Cornelia de lange syndrome with thyroid agenesis of an indonesian patient - Maskoen, A. M.; Laksono, B.; Hajjah, R.; Zada, A.; Suciati, L. P.; Fauziah, P. N.; Nataprawira, H. M. (Cellular and Molecular Biology, 2017)
Cornelia de Lange syndrome (CdLs), which is also called Brachmann de Lange syndrome, is a congenital disorder characterized by distinctive facial features, prenatal and postnatal growth deficiency, feeding difficulties, psychomotor delay, behavioral problems, and associated malformations that mainly involve the upper extremities. The prevalence ranges from 1:100,000 to as high as 1:10,000. Most cases (50-60%) were carried mutation in NIPBL gene. To our knowledge this is the first CdLs Indonesian case that reported with molecular analysis study. We present an 11 months old female Indonesian patient with classic CdLs with congenital hypothyroid. Genetics studies were performed in intron 1, exon 2, exon 10 and exon 22 of NIPBL gene. Thyroid studies (T3, T4, TSH and thyroid scan) were performed. Low level of T3 and T4, and high level of TSH were observed. Thyroid agenesis was found in thyroid scan examination. We detected thyroid agenesis which has been never reported in CdLs patients. We could not find any mutation in intron 1, exon 2, exon 10 and exon 22 of NIPBL gene. Further genetics examinations were necessary whether there is mutation in other locus.